MODIFIKASI PEMBENTUKAN LAPISAN Zn PADA PERMUKAAN BAJA DUAL FASA DENGAN NITRIDASI RINGAN - Arbi Dimyati (Pusbindiklat - LIPI, 2009)
In this work an experimental series was performed in order to modify the surface properties and galvanise ability of the dual-phase steel by the nitriding in an ammonia containing atmosphere (bright nitriding) during re-crystallisation annealing. The samples were characterized using various electron microscopy techniques and special preparation methods. The investigations show that during re-crystallization annealing with a relatively short duration because the nitrides formation with a large amount of nitrogen atoms can incorporate into the surface near area of the steel. The steel microstructures and the oxidation behavior of the alloying elements on the steel surface are positively changed. The decreasing of oxidation causes the surface activation that increases the steel/zinc reactions during hot-dipping. The formation of the Fe7415 inhibition layer also changes. The best quality of the zinc layer surfaces are achieved on the samples after annealing with ammonia concentration between 0.25 and 1 vol.-%. Therewith a new alternative for controlling the hot-dip galvaniseability of highstrength steels are proposed.